ANALISIS YURIDIS TERHADAP PENCEMARAN HUTAN MANGROVE PULAU PANNIKIANG DI KABUPATEN BARRU - Wahyu Rasyid, Nurhaedah Hasan, Hartono Hamzah, Syakiah (Madani Legal Review, 2022)
Mangrove forest ecosystems are natural resources that provide many benefits and advantages for humans, contributing to their high productivity and ability to preserve nature. Mangrove forests provide many ecological functions and that is why mangrove forests are one of the main producers of marine fisheries. The research entitled "Juridical Analysis of Pollution of Mangrove Forests on Pannikiang Island in Barru Regency", has a problem formulation of how to control the pollution of mangrove forest areas in Barru Regency and how the impact of mangrove forest pollution that occurs in Barru Regency. The purpose of this study was to determine the form of supervision of the pollution of mangrove forest areas in Barru Regency and to determine the impact of mangrove forest pollution that occurred in Barru Regency. This research uses descriptive qualitative research with an empirical normative approach. The source of the data used is to examine things that are theoretical by using secondary data, including the principles, rules, norms and legal rules contained in laws and regulations, studying books, and other documents that are closely related to this research. Based on this research, the monitoring of mangrove forests that have been carried out by the relevant agencies is currently not optimal and the impact of pollution of the mangrove forests of Pannikiang Island in the city of Parepare can be very detrimental both ecologically and socio-economically